Effectiveness Of Visual Imagery Techniques to Reduce Delinquency in Adolescents - Fitri, Hartika Utami; Maba, Aprezo Pardodi; Fatona, Ismi; Suryati, Suryati (Scidacplus, 2024)
Juvenile delinquency is a growing concern, particularly in urban areas. Effective intervention strategies, such as the Visual Imagery technique, are needed to address this issue. This study examines the effectiveness of the Visual Imagery technique in reducing juvenile delinquency in Lorong Prajurid Nangyu RT 03, Kelurahan 3/4 Ulu, Palembang. Using a descriptive quantitative approach, this study involved 23 adolescents selected through probability sampling. Data were collected through questionnaires (Visual Imagery Instrument, Cronbach's Alpha = 0.871), observation, and documentation, then analyzed using the Wilcoxon test with SPSS version 23. The results showed that before receiving group counseling, 12 adolescents (52.1%) exhibited high levels of delinquency. After the intervention, delinquent behavior decreased, with 13 adolescents (57%) categorized as having low delinquency levels. Statistical analysis yielded an Asymp. Sig (2-tailed) value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest results. Thus, the Visual Imagery technique is effective in reducing juvenile delinquency in the study area.